Review of Francisco X. Fernández Naval’s Novel Alma e o mar, from a Gender Perspective - Doval-Porto, Inma (Madrygal. Revista de Estudios Gallegos, 2018)
Francisco X. Fernández Naval’s novel, Alma e o mar, is analyzed from gender theories, focusing on language, narrative construction and topic. The study considers key aspects as non-normative sexualities, BDSM, patriarchal domination and symbolic and active violence. All these questions situate the novel close to a feminine writting or from female bodies and Queer narratives.